The Female Main Character’s Struggle against Gender-Based Subordination in Abi Daré’s The Girl with the Louding Voice - Claudia Anwar; Shita Dewi Ratih P; Agnes Setyowati (Journal Albion : Journal of English Literature, Language, and Culture, 2023)
This research discusses the struggle of the main character to get freedom in the novel The Girl with the Louding Voice by Abi Daré. The objective of this research is to reveal the gender-based discrimination in the form of subordination experienced by the main character. In addition, this research also shows the main character’s efforts to terminate the subordination and free herself from it. This qualitative research uses descriptive analysis method as well as library research through feminism perspective. The research finding reveals that the main character experiences gender-based discriminations in the form of subordination but eventually succeeds in getting her freedom.Keywords: freedom, subordination, feminism, struggle, female main character.